Comparative analysis of chloroplast genomes of 29 tomato germplasms: genome structures, phylogenetic relationships, and adaptive evolution - Wang, Xiaomin; Bai, Shengyi; Zhang, Zhaolei; Zheng, Fushun; Song, Lina; Wen, Lu; Guo, Meng; Cheng, Guoxin; Yao, Wenkong; Gao, Yanming; Li, Jianshe (Frontiers in Plant Science, 2023)
In order to compare and analyze the chloroplast (cp) genomes of tomato germplasms and understand their phylogenetic relationships, the cp genomes of 29 tomato germplasms were sequenced and analyzed in this study. The results showed highly conserved characteristics in structure, number of gene and intron, inverted repeat regions, and repeat sequences among the 29 cp genomes. Moreover, single-nucleotide polymorphism (SNP) loci with high polymorphism located at 17 fragments were selected as candidate SNP markers for future studies. In the phylogenetic tree, the cp genomes of tomatoes were clustered into two major clades, and the genetic relationship between S. pimpinellifolium and S. lycopersicum was very close. In addition, only rps15 showed the highest average KA/KS ratio in the analysis of adaptive evolution, which was strongly positively selected. It may be very important for the study of adaptive evolution and breeding of tomato. In general, this study provides valuable information for further study of phylogenetic relationships, evolution, germplasm identification, and molecular marker-assisted selection breeding of tomato.